Instructional technology as a tool in creating constructivist classrooms - Er, Neslihan Fatma; ER, MUSTAFA (Elsevier Science Bv, Sara Burgerhartstraat 25, Po Box 211, 1000 Ae Amsterdam, Netherlands, 2013)
Unlike traditional approach, constructivists view the learner as the active participant of the learning process. Constructivist instructors' main concern is providing the learners with learning environments in which they can engage in meaningful interactions. So, classrooms should be designed in such a way that the learners interpret and construct meaning based on their own experiences. Creation of rich learning environments via available technologies supporting constructivist learning platforms can be achieved through employing instructional strategies apt to the contextual variables. Teachers' new role is integrating technology into the curriculum so that learners build on their own experiences, construct their own meanings, create products, and solve problems successfully. (C) 2013 The Authors. Published by Elsevier Ltd.
Keywords: Technology; constructivist classroom; instruction; curriculum; Teknoloji; yapılandırmacı sınıf; talimat; Müfredat